Race, gender, and mental illness in the criminal justice system - Thompson, Melissa (Criminal justice recent scholarship, 2005)
Overview of the research -- The study of gender, race, mental illness, and crime -- Extending sociological theory -- Data, measures, and statistical procedures -- Predictors of psychiatric evaluation -- The effect of mental health evaluations on case outcomes -- Implications for theory and research on crime and mental illness.